1995
DOI: 10.1108/00346659510088654
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional effects of microwave cooking

Abstract: Several studies have shown that microwave cooking, if properly used, does not change the nutrient content of foods to a larger extent than conventional heating. In fact, suggests that there is a tendency towards greater retention of many micronutrients with microwaving, probably due to the shorter preparation time. Does not describe non-thermal effects. The main problem with microwaving is the uneven heating of the food, which has raised concern regarding microbiological safety. Microwaving infant formula and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Microwave radiation does not carry enough energy to ionize food molecules or to generate free radicals [13]. The basic principle of the process is the baking by molecular vibration that Effects of Radiation Technologies on Food Nutritional Quality http://dx.doi.org/10.5772/intechopen.80437 penetrates superficially in the foods, and the depth of penetration ranges from 2 to 4 cm.…”
Section: Microwave Radiationmentioning
confidence: 99%
“…Microwave radiation does not carry enough energy to ionize food molecules or to generate free radicals [13]. The basic principle of the process is the baking by molecular vibration that Effects of Radiation Technologies on Food Nutritional Quality http://dx.doi.org/10.5772/intechopen.80437 penetrates superficially in the foods, and the depth of penetration ranges from 2 to 4 cm.…”
Section: Microwave Radiationmentioning
confidence: 99%
“…Some studies had also shown that microwave heating affects the nutrient compounds in food (proteins, vitamins, etc.) less than conventional cooking because preparation time is shorter and less water is used (Lassen and Ovesen 1995; Marconi et al. 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Microwave (MW) heating, by allowing direct and homogenous heating of the milk volume, as well as high temperature and short time processing (Orsat et al, 2005) should improve the milk quality parameters. Indeed, several authors have shown the potential of MW heating (pasteurization, blanching, drying..) highlighting interesting results regarding food nutritional quality and preservation (Lefeuvre, 1994;Lassen and Ovesen, 1995;Kostaropoulos and Saravacos, 1995;Decareau, 1994;Gundavarapu et al, 1995;Laguerre et al, 1999). Similarly, Laguerre et al (1999) have demonstrated the interest of microwave-hot air coupling for bacterial destruction during MW drying of onions.…”
Section: Introductionmentioning
confidence: 97%